Pemanfaatan Tanaman Herbal Sebagai Obat Tradisional Pada Masyarakat Tompobulu Kabupaten Bantaeng - Ismi Wulandari; Mubarak Dahlan; Mrs. Nurlela (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to identify and recognize the use of herbal ingredients as traditional medicine in the Tompobulu community, Bantaeng Regency, community responses related to the development of knowledge on aspects of using herbal plants as traditional medicine, and community efforts to preserve their traditional knowledge about herbal plants. This research is a type of qualitative research that is written descriptively. Data collection techniques were carried out using observation, interviews, and documentation methods involving as many as 18 (eighteen) informants. The results of the study show that: (1) the Tompobulu community recognizes and utilizes herbal medicinal ingredients cannot be separated from the role of sanro and the knowledge of the community itself who seeks out through smart people or electronic media about the efficacy of a type of plant for health; (2) The response of the Tompobulu community to the growth and development of knowledge of herbal medicine starts from the yard of the house where they live which is used to plant herbal medicine or grows wild in the yard, this is the first prevention or treatment for their family against a disease. The lifestyle of returning to nature brings people to use herbal medicinal ingredients and make their own ingredients to maintain health; and (3) Efforts to preserve traditional knowledge carried out by the community through the cultivation of medicinal plants and the process of education from generation to generation both on how to use and efficacy of herbal plants on the human body.